OP0118 Development of The Eular Recommendations for The Use of Imaging in The Clinical Management of Osteoarthritis. (15th July 2016) - Sakellariou, G.; Conaghan, P.G.; Zhang, W.; Bijlsma, J.W.J.; Boyesen, P.; D'Agostino, M.A.; Doherty, M.; Fodor, D.; Kloppenburg, M.; Maeder, J.; Miese, F.; Naredo, E.; et al.
Abstract : Background: The increased availability of modern imaging in clinical practice has led to its more extensive use. In the field of osteoarthritis (OA), recommendations on the use of imaging in clinical trials have been developed, but there has been less focus on routine clinical management. Objectives: To develop evidence-based recommendations for the use of imaging in the clinical management of OA. Methods: A task force convened by the European League Against Rheumatism including rheumatologists, radiologists, generalists, methodologists and patients from 9 countries developed recommendations based on both evidence obtained through systematic literature review (SLR) and expert opinion. The task force initially identified the areas of application of imaging in OA and developed research questions to drive the SLR. Imaging modalities included were conventional radiography, ultrasound, magnetic resonance imaging, computed tomography, radioisotope scan. Anatomical areas of interest were knee, hip, hand and foot. Based on the priorities identified by the task force, the role of imaging in making a diagnosis of OA and identifying OA features (including soft tissue, bone and cartilage involvement), in detecting alternative diagnoses, the impact of imaging on disease management, in defining prognosis (natural history of the disease and response to treatment), in the follow up of the disease and to guide treatment were addressed. Research evidence was searched systematically for each question and separately for each anatomic area using PubMed and Embase. Results: The systematic review retrieved 6858 references, after the assessment of 1317 full papers, 380 studies were included. The results of the systematic review were presented to the task force, and consensus recommendations derived. These cover areas such as (exact wording not included for brevity reasons): the lack of need for imaging in diagnosis of patients who present with usual OA symptoms; role of imaging in differential diagnosis; consideration of the challenges in using imaging for routine monitoring of OA where there is no change in clinical status; what should be the feasible first choice modality and what issues were relevant to how images were acquired; how anatomical site of OA may influence use and type of imaging; and the role of imaging and intra-articular injection. Significant gaps in the literature underpinned the recommendations for future research that were also developed. Conclusions: Based on the results of a SLR and expert opinion, recommendations on the use of imaging in the clinical management of OA were developed. Disclosure of Interest: None declared